Film Thickness of Lithium Battery Fast De-Noising Based on Atomic Sequence Template Library - Gong Chen; Xifang Zhu; Qingquan Xu; Ancheng Xu; Hui Yang (Institute of Advanced Engineering and Science, 2014)
The natural frequency and scanning vibration frequency of C-dynamic scanning system of laser sensors are acquired for film thickness of lithium battery de-noising based on multi-resolution wavelet algorithm. For this reason, fast de-noising based on atomic sequence template library is present .First, under various mode of scanning, best atomic sequence template is built by sparse decomposition. Secondly, at the given mode, film thickness data is match to the best atomic sequence to de-nosing. Experimental results show that template-matching pursuit(MP) algorithm is effective and algorithm speed is higher than MP 57 times.